Anioł w piśmiennictwie polskim XVII i XVIII wieku - Dybek, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The work is devoted to the presence of angelic themes in the literature of Polish Baroque and Enlightenment. It is not a monograph on the subject, due to the great extent of the topic (there are thousands of angelic motives in that period of time). However, it addresses the most important threads regarding messengers of God. It is focused on the texts written in the seventeenth and eighteenth centuries in order to verify to what extent the intellectual breakthrough of the Enlightenment changed the attitude of authors towards angelology.The work is composed of eight parts. Th e introduction includes the explanation with regard to the texts that have been analyzed. Th ey are mostly religious texts (sermons, treatises), which were forming the consciousness of an average Christian in the two centuries (even though theyare not prominent works). In this way one can fi nd out what an average author and reader/ listener knew about the angels. Part two contains information on the sources that could have been usedby the authors in the Baroque and Enlightenment. Th ese sources included the Bible (though, it refersto the angels sporadically and incon sistently), Apocrypha (Jewish, Christian as well as Egyptian) and theology (especially the teachings of Pseudo-Dionysius and St. Th omas Aquinas). Part two also contains a brief over view on medieval and Renaissance literature regarding angelic motives. It endswith a description of one of Baroque compendium on the angels, entitled Angelic righteousness by M.I. Tłuczyński.Part three is devoted to two issues.
Keywords: anioły; piśmiennictwo polskie - 17 -18 w.; angelologia